Genetic polymorphisms influence the susceptibility of men to sperm DNA damage associated with exposure to air pollution - Rubes, J; Rybar, R; Prinosilova, P; Veznik, Z; Chvatalova, I; Solansky, I; Sram, R J (Mutation research, 2010)
The purpose of the present study was to investigate the impact of carcinogenic polycyclic aromatic hydrocarbons and volatile organic compounds on sperm quality in a group of city policemen in Prague during a period of increased concentrations of ambient air-pollutants (winter season) compared to a period of low exposure (spring). Polymorphisms in metabolic genes (CYP1A1, EPHX1, GSTM1, GSTP1, GSTT1), folic acid metabolism genes (MTR, MTHFR) and DNA repair genes (XRCC1, XPD6, XPD23, hOGG1) were evaluated in these men as potential modifiers of associations between air pollution exposure and changes in sperm quality. The study population was a group of 47 policemen working in the center of the city. Seasonal differences in exposure were verified by ambient and personal monitoring. Markers of sperm injury included semen volume, sperm concentration, sperm morphology, sperm motility, and sperm DNA damage measured with the sperm chromatin structure assay The sperm chromatin structure assay (SCSA) includes a measure of DNA damage called DNA Fragmentation Index (DFI). The % of cells with detectable DFI (detDFI) by this assay includes sperm with either medium or high DNA damage; the term hDFI is used to define the % of sperm with only high DNA damage. The assay also detects immature sperm defined by high density staining (HDS). No significant differences were found in any of the standard semen parameters between the sampling periods except for vitality of sperms. Both DFI and HDS were significantly higher in winter than in spring samples for all men and for non-smokers. At the bivariate level, significant associations between hDFI or detDFI and polymorphisms of the repair genes XRCC1, XPD6 and XPD23 were observed. In multivariate models, polymorphisms of the genes XPD6, XPD23 and CYP1A1MspI were associated with hDFI and HDS. Moreover, HDS was significantly associated with polymorphisms in GSTM1 gene.
Keywords: kouření; DNA Damage; DNA Repair Enzymes; Police; genotyp; Male; Folic Acid; Cotinine; lidé; Genotype; polymerázová řetězová reakce; Polymerase Chain Reaction; poškození DNA; polymorfismus délky restrikčních fragmentů; glutathiontransferasa; fragmentace DNA; DNA Fragmentation; mužské pohlaví; Chromatin; cytochrom P-450 CYP1A1; Adult; polymorfismus genetický; kyselina listová; enzymy opravy DNA; Glutathione Transferase; Smoking; Polymorphism, Genetic; Air Pollutants, Occupational; xeroderma pigmentosum - protein skupiny D; kotinin; Humans; Polymorphism, Restriction Fragment Length; Xeroderma Pigmentosum Group D Protein; chromatin; dospělí; látky znečišťující vzduch v pracovním prostředí; policie; Spermatozoa; spermie; Cytochrome P-450 CYP1A1